PENGGUNAAN MEDIA GAME KAHOOT UNTUK MENINGKATKAN HAFALAN MUFRODAT SISWA KELAS X MAN 1 KOTA GORONTALO - Sumani, titik nor sa'idah nor (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2024)
The Arabic language lessons encompass various branches and topics. Among the aspects that a student of Arabic must understand are the components or elements of the Arabic language itself. To prevent the learning process from becoming monotonous, the application Kahoot can be a solution that can be implemented. This research aims to determine whether the Kahoot game application is effective in improving students' memorization of vocabulary. This study employs qualitative descriptive research. Data collection techniques include observation, interviews, and questionnaires. The results of this study indicate that Kahoot is effective in Arabic language learning and can enhance the memorization of vocabulary for 10th-grade students at MAN 1 Kota Gorontalo. The advantages of using the Kahoot application in teaching include motivating students, minimizing cheating, and making it easier for teachers to evaluate and grade. On the other hand, the drawbacks of using the Kahoot application in Arabic language teaching are its inability to function in the presence of internet network disruptions or the absence of a network altogether. Additionally, teachers need to develop their own strategies for engaging students during the test administration.